Information content of analysts' report: a literature survey - Mohd Thas Thaker, Hassanudin; Mohamad, Azhar; Mustaffa Kamil, Nazrol Kamil; Duasa, Jarita (Faculty of Economic and Business Syarif Hidayatullah State Islamic University Jakarta, 2018)
The objective of this paper is to survey the literature on information content of analyst report from three important dimensions, namely, target price, earnings forecast and trading volume. The methodology employed is following the qualitative approach by reviewing and examining the past literature from the view of theoretical and empirical researches. The initial result from existing literature, reveals that the research in analyst report mainly focused on empirical research rather than theoretical perspective. Secondly, there no clear consensus on the consistency of results in terms of how well the information contents involving target price, earnings forecast and trading volume influencing the stock return. Thus, the views whether analyst report transmitting information to the investors is still remain unambiguous when making investment decision. This study is expected to enrich the existing literature in the area of analyst report and propose several areas for future researches related to this topic.